Using Grid as Teaching Strategy in Teaching Mathematics - Magnaye, Rosemarie; Magnaye, Aries (JPAIR Institutional Research, 2019)
This paper analyzes how Grid as a graphic organizer can significantly improve the numeracy level in Mathematics of the Grade 3 pupils in addition and subtraction and identify common errors and misconceptions in adding and subtracting whole numbers. To answer this question, we compared the performance of Grade 3 pupil participants. Fifty-six percent (n= 39) from Jose Rizal Memorial School and forty-four percent (n=31) from San Juan Elementary School. Out of 70 pupils, 57 or 81.43% belonged to the non-numerate level, 13 or 18.57% were classified as instructional and non-numerate. The descriptive design was utilized. The data were analyzed using mean, frequency count, percentage, and z-test in determining the effect of the grid as a graphic organizer on the numeracy level of Grade 3 Pupils. The results of the study indicate that the numeracy level of Grade 3 pupils after using the grid as a graphic organizer revealed that the non-numerate pupils were lessened to 23 out of 70 or 32.86%, instructional pupils increased to 27 or 38.57% and numerates became 20 or 28.57%. The computed mean was increased to 5.87, having a scale description of the instructional level. The findings suggest that Grid as a graphic organizer helped a lot in proper alignment of numbers to avoid common errors and misconceptions and was found to be an effective teaching strategy in teaching Mathematics.